1974
DOI: 10.1172/jci107734
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Anti-Glomercular Basement Membrane Antibodies by a Radioimmunological Technique CLINICAL APPLICATION IN HUMAN NEPHROPATHIES

Abstract: A n S T R A C T A radioimmunoassay for detection of anti-glomerular basement membrane (GBM) antibody was set up with a 70,000 mol wt GBM antigen, labeled with Iodine-'I and containing both types of oligosaccharidic chains present in the whole membrane.Separation of free radioactive antigens from antigens bound to immunoglobulins was obtained by precipitation with polyethylene glycol (mol wt, 6,000), at a final concentration of 20%. In the presence of normal human or rabbit sera, less than 20% of labeled antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Results were expressed as percent 125I-Clq precipitated when compared with the total protein bound radioactivity obtained by 20% (wt/vol) trichloroacetic acid precipitation of 50 ml of normal human serum mixed with 50 ml of 125I-Clq. To avoid variations resulting from the use of different batches of 125I-Clq, the results were corrected, using a modified Farr's formula, for the precipitation of radiolabeled Clq observed in presence of normal serum (21).…”
Section: Methodsmentioning
confidence: 99%
“…Results were expressed as percent 125I-Clq precipitated when compared with the total protein bound radioactivity obtained by 20% (wt/vol) trichloroacetic acid precipitation of 50 ml of normal human serum mixed with 50 ml of 125I-Clq. To avoid variations resulting from the use of different batches of 125I-Clq, the results were corrected, using a modified Farr's formula, for the precipitation of radiolabeled Clq observed in presence of normal serum (21).…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that a proportion of patients with glomerulonephritis have antibodies against extracts of glomerular basement membrane (GBM) (1,2). In particular, 6 M guanidine hydrochloride extracts contained antigens reacting with antibodies from patients with Goodpasture syndrome, systemic lupus erythematosus nephritis, or IgA nephropathy.…”
mentioning
confidence: 99%
“…Based on the use of immunodiffusion to determine antibodies in sera from patients suffering from kidney disease and R1A [4] it has been suggested that the antigenic deter minants responsible for immunization are located in noncollagen components of the GBM. Other studies have indicated, how ever, that some patient sera react with small peptides containing the glucose-galactose disaccharide of collagen [5], Therefore, the precise specificity of these antibodies has not been demonstrated. The fact that immunoreactive basement membrane components are very heterogenous irrespective of the solubilization method used [6] makes it dif ficult to obtain distinct antigens which are not contaminated with other antigens.…”
Section: Introductionmentioning
confidence: 99%